Correlation between the seropositivity of cytotoxinassociated gene a h. Pylori and the gastritic severity degree in patients with dyspepsia - P. H. Hidayati (Yerevan State Medical University, 2019)
Background: The pathogenesis of dyspepsia associated with gastritis due to H. pylori infection remains unclear. Protein Cytotoxin-associated gene A (CagA) H. pylori is known to play an important role in the occurrence of more severe gastritis. Patients, infected with H. pylori with positive CagA were found to have a tendency to experience peptic ulceration and the development of gastric mucosal progression. Objective: To analyze the association of seropositivity of CagA H. pylori with the severity of gastritis in dyspeptic patients. Methods: This is a cross-sectional study involving all dyspepsia patients undergoing endoscopy and gastric biopsy in the endoscopic unit of the Internal Medicine Department of Dr Soetomo General hospital Surabaya. The assessment of the gastritis severity degree was performed using the updated Sydney System classification (inflammation, neutrophil infiltration, glandular atrophy, and intestinal metaplasia). As for the detection of CagA H. pylori was used serum serology. Results: From all 34 patients with dyspepsia, 8 (23.5) was positive of H.pylori patients and 4 (50) patients were positive of CagA H.pylori. Inflammatory scores and neutrophil infiltration in the positive CagA H.pylori group were significantly higher than in the negative, H.pylori group and the positive Caga negative H.pylori group. While on the scores of gland atrophy and intestinal metaplasia, there was no difference between the three groups. There was no statistically significant association between CagA H. pylori seropositivity with inflammatory score, neutrophil infiltration, gland atrophy and intestinal metaplasia. Conclusion: There was no statistically significant correlation between CagA H. pylori porosopositivity and the severity of gastritis according to Updated Sydney Systems in both the inflammatory categories, neutrophil infiltration, gland atrophy and intestinal metaplasia. Â© 2019, Yerevan State Medical University. All rights reserved.